GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN GIGI DAN MULUT DI POLI GIGI UPT PUSKESMAS CIBALIUNG (Jurnal Kesehatan Siliwangi, 2021)
Cibaliung Health Center as a first-level health service facility which is a benchmark for the success of health development should be able to provide good service quality so that it can provide satisfaction to patients. Patient satisfaction is obtained if the services provided are in accordance with their expectations. Objective: This study aims to determine the description of patient satisfaction with dental and oral health services at the Dental Poly UPT Cibaliung Health Center, Pandeglang City. Metode : This research is descriptive research. The sampling technique was carried out using an accidental sampling technique with a sample of 60 respondents. Data processing is carried out using a frequency distribution table of all answers filled out by respondents. Results: The results of the study on the description of patient satisfaction with dental and oral health services at the Dental Poly UPT Puskesmas Cibaliung illustrates that patient satisfaction with the satisfaction of the reliability of health workers in providing services with the largest percentage of the score is 98%, on the satisfaction of the response of health workers with a percentage of the total score of 100% on facilities and infrastructure with a percentage of the total score of 98% which states that respondents are satisfied with the services provided. Conclusion: that respondents are satisfied with the services provided.